2004
DOI: 10.1080/08958370490427932
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Allergy to Trimellitic Anhydride in Rats: Concentration-Response Relationships During Elicitation

Abstract: The present study investigated whether airway responses of sensitized rats to trimellitic anhydride (TMA) were concentration dependent and whether these were related to irritation by TMA. Groups of BN and Wistar rats were sensitized by two dermal applications of TMA (50% w/v, followed by 25% w/v in vehicle). Controls received vehicle (acetone-olive oil 4:1, v/v). All animals were challenged 3 wk after the first sensitization by inhalation of one of a range of concentrations of TMA (0.2-61 mg/m3 for BN rats, 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 23 publications
(36 reference statements)
6
18
0
Order By: Relevance
“…Moreover, the accumulation of inflammatory cells appears to be a more sensitive indicator of the allergen dose used for challenge than AHR: intranasal challenge with 10 lg of ovalbumin induced significant accumulation of inflammatory cells, whereas AHR to methacholine in this group was not detected. Similar to our results, inflammatory cell accumulation was also shown to be more sensitive than AHR to antigen dose used for challenge in two other animal models, allergic responses to an extract of Penicillium chrysogenum in BALB/c mice [24], and to trimellitic anhydride in Brown Norway rats [25]. The described model, therefore, closely resembles clinical observations and represents an elegant experimental system that could provide insights in the mechanisms by which inflammation transiently enhances AHR after allergen challenge.…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, the accumulation of inflammatory cells appears to be a more sensitive indicator of the allergen dose used for challenge than AHR: intranasal challenge with 10 lg of ovalbumin induced significant accumulation of inflammatory cells, whereas AHR to methacholine in this group was not detected. Similar to our results, inflammatory cell accumulation was also shown to be more sensitive than AHR to antigen dose used for challenge in two other animal models, allergic responses to an extract of Penicillium chrysogenum in BALB/c mice [24], and to trimellitic anhydride in Brown Norway rats [25]. The described model, therefore, closely resembles clinical observations and represents an elegant experimental system that could provide insights in the mechanisms by which inflammation transiently enhances AHR after allergen challenge.…”
Section: Discussionsupporting
confidence: 70%
“…In confirmation with previous studies, TMA-induced apneas and allergic laryngitis, increased inflammatory cell numbers in BAL, altered breathing frequency, and elevated IgE levels in serum and lung (Arts et al 1998;Arts et al 2004;Valstar et al 2006).…”
Section: Discussionsupporting
confidence: 75%
“…The acetone concentration was kept between 3,000 and 5,000 ppm (~7-12 g/m 3 ), which levels are far below the level inducing sensory irritation (Alarie 1973;De Ceaurriz et al 1981;Schaper and Brost 1991) and which indeed did not induce changes in breathing pattern in either sensitized or unsensitized rats (Arts et al 1998). The challenge concentration of TMA was based on a previous study performed in BN rats (Arts et al 2004). Atmospheric concentrations of TMA were determined gravimetrically by filter sampling, and those of acetone, by calculations based on the nominal concentration, assuming the usual 100% generation efficiency for this vapor.…”
Section: Atmosphere Generation and Analysismentioning
confidence: 99%
“…13 Recently it has also been shown that Brown Norway rats dermally sensitized to TMA had asthma-like early and late changes in breathing pattern after airway exposure to TMA. 12,14,15 DNCB is a typical dermal sensitizer that elicits contact hypersensitivity mediated by T H 1 cytokines, such as IFN-g and IL-12, 16 and it does not appear to cause occupational asthma or allergic rhinitis. 17 The primary objective of this study was to examine the capability of our previously described mouse model of chemical-induced asthma 18,19 to discriminate between a respiratory sensitizer (TMA) and a dermal sensitizer (DNCB).…”
mentioning
confidence: 99%
“…10 TMA is a respiratory sensitizer in human subjects, 11 but it is also capable of inducing airway irritation in animals. 12 It has been shown that high doses of TMA, when applied to the skin, preferentially induce a T H 2 response, with increased levels of IL-4, IL-10, and IL-13 and relatively low amounts of the T H 1 cytokine IFN-g in draining lymph nodes. 13 Recently it has also been shown that Brown Norway rats dermally sensitized to TMA had asthma-like early and late changes in breathing pattern after airway exposure to TMA.…”
mentioning
confidence: 99%